Developing an approach for assigning GRADE levels in a systematic overview of reviews of diagnostic test accuracy using general principles identified from current GRADE guidelines: A case study - Dullea, Andrew; Smith, Susan (My University, 2025)
Existing guidelines on overviews of reviews and umbrella reviews recommend an assessment of the certainty of evidence, but provide limited guidance on ‘how to’ apply the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) to such a complex evidence synthesis. We share our experience of developing a ‘general principles’ approach to applying GRADE to a complex overview of reviews. The approach was developed in an iterative and exploratory manner during the planning and conduct of an overview of reviews of a novel molecular imaging technique for the staging of prostate cancer, involving a formal review by a group of 11 methodologists/health services researchers. This approach was developed during the evidence synthesis process, piloted, and then applied to our ongoing overview of reviews. A ‘general principles’ approach of applying the domains of GRADE to an overview of reviews and arriving at an overall summary judgement for each outcome is presented. Our approach details additional factors to consider, including addressing both the primary study risk of bias as assessed by the included reviews and the risk of bias of the systematic reviews themselves, as well as the statistical heterogeneity observed in meta-analyses conducted within the included reviews. Our approach distilled key principles from the relevant GRADE guidelines and allowed us to apply GRADE to a complex body of evidence in a consistent and transparent way. The approach taken and the methods used to develop our approach may inform researchers working on overviews of reviews, umbrella reviews, or future methodological guidelines.
PUBLISHED
Published online
Keywords: GRADE; overview; research synthesis; review of reviews; systematic review; umbrella review; Epidemiology; Public health